A new species of the genus Astragalus (Leguminosae-Papilionoideae) from Iran - Bagheri, Ali; Rahiminejad, Mohammad Reza; Maassoumi, Ali Asghar (Phytotaxa, 2014)
As a result of a recent expedition to the north-west of Iran, we describe here a newly dicovered species, Astragalus makuensis, belonging to sect. Hymenostegis. The new species is described and illustrated with a line drawing, and compared with its most closely related species A. hymenocystis and A. pereshkhoranicus. The new species is endemic to the western Azarbayejan province of Iran.